EFFECTIVENESS OF CONSERVATIVE TREATMENT IN THE MANAGEMENT OF SECRETORY OTITIS MEDIA - Malik, Sohail Ahmad; Muhammad, Raza; Yousaf, Muhammad; Shah, Imran (Journal of Ayub Medical College Abbottabad, 2014)
Background: Secretory otitis media is a very important and common ENT disease, especially in the children. The aetiology of Secretory otitis media is multifocal, and the treatment is initially medical or conservative and if it fails then surgery is indicated. The objective of the study was to determine the efficacy of medical treatment in the management of Secretory otitis media. Methods: This cross sectional descriptive study was conducted at the outpatient department of ENT, Ayub Medical Institute (AMI) Abbottabad, from Mar to Sep 2013. A total of 40 patients were included in this study and standard medical treatment of secretory otitis media was given. The patients were followed up at 2nd and then 4th week and results were analysed. Results: Both clinical and audiological diagnosis of secretory otitis media was made and patients were followed up at 2nd and 4th week to see the effect of treatment. Among 40 patients, 26 (65%) completely recovered from the disease while 14 patients (35%) did not improve. Conclusion: Conservative treatment is effective in the management of Secretory otitis media. Keywords: Secretory otitis media, Conservative Treatment, effectiveness